Metacognitive Therapy for Posttraumatic Stress Disorder in Youth: A Feasibility Study - Simons, Michael; Kursawe, Anna-Lena (Frontiers in Psychology, 2019)
Metacognitive therapy (MCT) is an effective treatment for posttraumatic stress disorders (PTSD) in adults. However, there is no evidence for the feasibility, acceptability, and efficacy of MCT for PTSD in youth so far. This study is the first to utilize MCT for children and adolescents with PTSD. Twenty-one children and adolescents (aged 8–19 years) who were consecutively referred to the outpatient trauma clinic were treated with MCT. In all patients, treatment was well accepted and regularly attended. At post-treatment, MCT was associated with significant and large reductions in posttraumatic stress symptoms. Depending on the outcome measure, 95% or 85% of the patients were classified as recovered after treatment. Eighteen patients were included in the calculation of the overall outcome. Effect sizes on primary PTSD measures were large (Cohen’s d = 3.42 and d = 1.92) and more than comparable to well-established treatments. Only 6 patients were available at follow-up, but their improvements were found to be stable. Despite the limitations of this uncontrolled study, the results suggest that MCT may be a feasible and promising treatment for traumatized children and adolescents and they justify a controlled trial evaluating the efficacy of MCT versus an already well-established intervention.